Relationship between job design characteristics and citizen behavior - Anawi Rhiyo, Sahar; Radhi Athab, Khawlah (Opción, 2019)
The study highlights the importance of Job Design Characteristics and Citizen Behavior through the Intermediate Role of Perceived Organizational Support in the Higher Educational sector of Pakistan. In this study, the researcher used positivism research philosophy. Stratified sampling technique was used, and data were collected through standardized questionnaire all universities of Pakistan. The results showed that perceived organizational support has an intermediating role relationship between job design characteristics and citizen behavior. This is the first study that examines the relationship between job design characteristics and citizen behavior in the Higher Educational sector of Pakistan.